Perancangan Dan Pembuatan Aplikasi Decision Support System Pada Departemen Hrd Dan Pembelian Dengan Menggunakan Metode Analytical Hierarcy Process (AHP) - Setiawan, Alexander; Irawan, Muhammad Isa; Wijaya, Robin (Jurnal Semesta Teknika, 2007)
The rapidly technology process on globalisasion era in business world, makes the decision making is the important thing to make decision faced with the competition in business world. The decision making can be influence by a few aspect and group, which can influence the decision maker to accelerate the fast, perfectly and correctly the decision making. This software created by using Analytical hierarcy process method is doing calculation proses to get the best decision, using the score group of calculation and compare it with each possibility count of the choosen decision, this software specially for HRD and purchasing division, for HRD division this software will be use to decide which employee will be promoted or which employee will be fired. For purchasing division, this software will used to decude which supplier will be choose to buy a kind of goods. Employee mark, disipline mark, and development ability are the group that used for HRD division, while purchasing division use quality of goods, price, accuracy time shipping and supplier identity.Application the design and the testing of decision support system result a correct and flexsibel decision with all criteria which influence that decision and give a report in order to user can understand why this software choose that decision.